Possibilities for Growing Fennel in Hungary - Cserni, Imre; Kovács, Noémi (Acta Agraria Debreceniensis, 2002)
Fennel appers to be cupable of enlarging our vegetable sortiments in Hungary. Ecological conditions favour production. For cultivation, 12,5 plants/m2 are recommended. Fennel requires 250-300 mm water over a 110 day growing period. No considerable pests have been found yet. 1-3 kg/m2 tubers can be harvested. Marketable tubers weigh 200-300 g. Smaller tubers can be dried, pickled or deep frozen.